Growth of Caesalpinia platyloba S. Watson plant growth in nursery under different organic substrates - Velázquez Roblero, Raúl Emanuel; Martínez Álvarez, Iván Guadalupe; Prieto Ruiz, José Ángel; Félix-Herrán, Jaime Alberto (Ecosistemas y Recursos Agropecuarios, 2025)
Caesalpinia platyloba S. Watson is a multipurpose species native to the tropical deciduous forest and of great interest for reforestation and establishment of agroforestry systems. The objective was to evaluate the effect of different organic substrates on the development of Caesalpinia platyloba seedlings. Were considered the variables height, stem diameter, fresh and dry biomass of foliage, and roots in germination tray; in polyethylene cups (15 days after the sowing), transplant survival and plant quality indices were considered. It was found that solid waste compost and vermicompost improve the quality of Caesalpinia platyloba seedlings by improving the stem diameter and height ratio, as well as the lignification index of the plant, thus increasing the Dickson quality index. The 50%-50% compost or vermicompost-vermiculite mixture can be used as a substrate to produce Caesalpinia platyloba plants.